Estudos estruturais de compostos de telúrio e de docking em catepsinas B, K, L, S - Maganhi, Stella Hernandez (2013)
Cathepsins are lysosomal cysteine proteases responsible for protein turnover in our organism. In non-lysosomal environment they are related to a number of diseases such as cancer, Alzheimer, autoimmune diseases and osteoporosis. Tellurium compounds have proved to be promising therapeutic agents against these diseases due to inhibition of the proteases through the formation of a Te S covalent bond with the sulfur of a catalytic cysteine. In this work the crystal and molecular structures of compounds (ptol)Te[C(H)=C(Cl)Ph]X2 (X = Cl, Br, I), butyldiiodo[(1Z)-(2- iodopent-1-en-yl)-4- tellane and their docking in Catepsine B are described. The results showed that these compounds, whose activity has not been measured, should have an inhibitory activity very similar to that of a known compound with a close structure. Moreover, it is shown that the substitution of a phenyl group for an aliphatic one should not have any influence on the activity of these kind of compounds. Also the structures of a series of dipnones were determined which were used as basis for the molecular modeling of others that could not be crystallized and for the docking studies in catepsins B, K, L and S. The results allowed establishing a model that explains their different inhibitory activities.